Preparation and characterization of a new graphite superconductor: Ca0.5Sr0.5C6 - Saki Nishiyama (Nature Portfolio, 2017)
Abstract We have produced a superconducting binary-elements intercalated graphite, CaxSr1−xCy, with the intercalation of Sr and Ca in highly-oriented pyrolytic graphite; the superconducting transition temperature, T c, was ~3 K. The superconducting CaxSr1−xCy sample was fabricated with the nominal x value of 0.8, i.e., Ca0.8Sr0.2Cy. Energy dispersive X-ray (EDX) spectroscopy provided the stoichiometry of Ca0.5(2)Sr0.5(2)Cy for this sample, and the X-ray powder diffraction (XRD) pattern showed that Ca0.5(2)Sr0.5(2)Cy took the SrC6-type hexagonal-structure rather than CaC6-type rhombohedral-structure. Consequently, the chemical formula of CaxSr1−xCy sample could be expressed as ‘Ca0.5(2)Sr0.5(2)C6’. The XRD pattern of Ca0.5(2)Sr0.5(2)C6 was measured at 0–31 GPa, showing that the lattice shrank monotonically with increasing pressure up to 8.6 GPa, with the structural phase transition occurring above 8.6 GPa. The pressure dependence of T c was determined from the DC magnetic susceptibility and resistance up to 15 GPa, which exhibited a positive pressure dependence of T c up to 8.3 GPa, as in YbC6, SrC6, KC8, CaC6 and Ca0.6K0.4C8. The further application of pressure caused the rapid decrease of T c. In this study, the fabrication and superconducting properties of new binary-elements intercalated graphite, CaxSr1−xCy, are fully investigated, and suitable combinations of elements are suggested for binary-elements intercalated graphite.